مقترحات لزيادة دعم استقلالية المراجع الخارجي - عوينات، فريد; كويسي ،محمد; مايدة، محمد فيصل (جامعة الوادي University of Eloued, 2025)
This study aims to clarify the most important factors affecting the external auditor's independence and to provide proposals to increase support for independence in Algeria. This study is based on three variables used to understand and analyze the level of audit quality, namely, audit committees, indirect payment of fees, and quality control. Data were collected by distributing questionnaires to 42 respondents from accountants and accounting experts in Algeria and processing them using the Statistical Package for the Social Sciences (SPSS) program. The study concluded that audit committees, indirect payment of fees, and quality control lead to increased emphasis on the important role they play in raising support for the independence of the external auditor.
Proposals to increase support for the independence of the external auditor The point of view of a sample of experts and the external auditors in Algeria
Keywords: جودة مراجعة; مراجع خارجي; استقلالية مراجع خارجي; مستخدمي معلومات محاسبية; Audit quality; external auditor; independence of external auditor; users of accounting information